2022
DOI: 10.5582/bst.2022.01343
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox – A danger approaching Asia

Abstract: Monkeypox, a zoonotic disease, was first identified in humans in the Democratic Republic of the Congo in 1970. In the 50 years since its inception, the monkeypox endemic was concentrated in Central and West Africa. Sporadic cases reported in Europe and North America were linked to imported cases (1). On May 7, 2022, a confirmed case of monkeypox was first reported in the United Kingdom, and several countries subsequently reported cases of monkeypox, spanning the globe from Europe to North America, Africa, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In 2022, atypical mpox outbreaks occurred in many non-endemic countries, including the US, Europe, the Middle East, the Western Pacific region, South Korea, and Japan [ 34 , 35 ]. Thornhill et al found that 98% of people diagnosed with mpox in 16 countries between April 27 and June 24, 2022 were gay or bisexual men [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, atypical mpox outbreaks occurred in many non-endemic countries, including the US, Europe, the Middle East, the Western Pacific region, South Korea, and Japan [ 34 , 35 ]. Thornhill et al found that 98% of people diagnosed with mpox in 16 countries between April 27 and June 24, 2022 were gay or bisexual men [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines for the prevention of MPX in high-risk groups or post-exposure prophylaxis are still smallpox-specific vaccines. The use of smallpox vaccine for MPX prevention is still mainly restricted to high-risk groups or health personnel who treat MPX, but mass vaccination against MPX has not been required or recommended [2]. Many patients infected with MPX have mild symptoms and can recover without any medical treatment [52].…”
Section: Vaccines and Treatmentmentioning
confidence: 99%
“…Since the end of June 2022, there has been a remarkable increase in the number of MPX cases globally. WHO has declared the MPX epidemic a worldwide public health emergency due to its re-emergence, re-emerging health threat, and potential spread [2]. By July 21, 2022, WHO declared 15,734 laboratories confirmed MPX infection cases in 75 countries on five continents.…”
Section: Introductionmentioning
confidence: 99%
“…MPXV contains a mutant F3L gene, 53 corresponding to a truncated version of VACV E3. However, due to extragenic or other causes, this MPXV‐specific protein is completely capable in function in inhibiting type I IFN responses 54 .…”
Section: Mpox Virus and Immune Cells And Moleculesmentioning
confidence: 99%